The Behavioral Factor Associated with The Incidence of Malariain Endemic Area - Zulaikhah, Siti Thomas; Etika, Dhanny Rona; Mashoedi, Imam Djamaludin (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: Magelang Regency is one of the endemic area of malaria in central Java. The working area of Health centre of Kajoran I, Banjaretno, has the highest incidence of malaria annually (Dinkes Magelang, 2010). Malaria is is transmitted through the bite of female Anopheles infected by Plasmodium sp. Its most effective prevention is vector eradication. This study was aimed at finding out the behavioral risk for the incidence of malaria.Design and Methods: In this observasional study using case control design include 40 cases and 40 controls using the simple random sampling. Chi square test followed by double-logistic regression was applied for the data analysis with p=5%. Results: Bivariate analysis on the 6 factors resulted in p<0.05 and 2 factors resulted in p>0.05. multivariate analysis showed that the habit factor of going out in the evening, installing wire gauze on the ventilation, hanging used clothes, mowing lawn, the existence of closed waste basket, washing the curtain resulted in the p=0.010 (OR = 10; 95% CI = 3.4-39.2), p=0.001 (OR = 4.1; 95% CI = 3.5-15.8), p=0.018 (OR = 3.3; 95% CI = 1.9 -16.2), p=0.044 (OR = 6.5; 95% CI = 2.1-30.9), p=0.380 (OR = 0.43; 95% CI = 0.1-1.2), p=0.002 (OR = 2.4; 95% CI =3.4 -5.6) respectively.Conclusion: The habit of going out in the evening has been shown to be most important behavioral factor associated with the malaria incidence (Sains Medika, 3(2):168-184).